2014
DOI: 10.1111/josh.12144
|View full text |Cite
|
Sign up to set email alerts
|

School‐Wide Programs Aimed at Obesity Among Latino Youth in the United States: A Review of the Evidence

Abstract: This review is the first to gather evidence-based research systematically aimed at obesity-related interventions in the school setting that are specifically focused on Latino children. Results of the review are promising and timely, given the exigency of the needed evidence, and the current state of childhood obesity in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…Therefore, this study's results taken in context with other BMI‐related interventions for Latino youth suggest that culturally salient, before or after school programs with curricula focusing on physical education and nutrition, beyond that introduced in school, may be sufficient to produce reductions in BMI in Latino children. This interpretation is consistent with recent reviews of school‐based obesity interventions targeted toward Latino populations, and stresses similar programmatic components to achieve desired BMI outcomes in these youth …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, this study's results taken in context with other BMI‐related interventions for Latino youth suggest that culturally salient, before or after school programs with curricula focusing on physical education and nutrition, beyond that introduced in school, may be sufficient to produce reductions in BMI in Latino children. This interpretation is consistent with recent reviews of school‐based obesity interventions targeted toward Latino populations, and stresses similar programmatic components to achieve desired BMI outcomes in these youth …”
Section: Discussionsupporting
confidence: 89%
“…In response to literature citing low‐income, ethnic minority, urban youth as the most at risk for developing obesity, some recent school‐based interventions targeted such populations . Most of the studies that showed significant effects reducing, attenuating, or maintaining BMI‐related outcomes have been conducted with Hispanic children . Fewer studies have been conducted with primarily African American youth with even fewer demonstrating significant BMI‐related effects.…”
mentioning
confidence: 99%
“…Studies directly comparing Latino and white children are limited; nonetheless, there are findings which revealed that considerable ethnic differences exist in PA participation patterns. Latino Americans, for instance, have higher obesity rates compared to non‐Hispanic Whites . A study on sixth grade students also revealed that Latino children exhibited lower levels of moderate‐to‐vigorous intensity PA compared to other racial or ethnic groups .…”
Section: Differences Between Latino and White Childrenmentioning
confidence: 99%
“…In a systematic review of physical activity interventions in Latin America, Hoehner et al 42 and Lobelo et al 43 reported that physical education classes in elementary school are effective in increasing physical activity levels among children. Furthermore, school-based and health care based interventions have also been shown to be effective for the prevention and management of obesity in Latin America and among Latinos in the US 44,45 . This highlights the need for encouraging the development and implementation of physical activity referral programs for children and young people by ensuring coordination between the primary health care system and schools.…”
Section: Variablesmentioning
confidence: 99%